Conflicts of Professional Ethics and Data Privacy in the Digital Era - Amiruddin; Inun Suryani Harahap; Ahmad Prayogi; Nadia, Nadia Muntaja (Cattleya Darmaya Fortuna, 2024)
This research aims to investigate the conflict between professional ethics and data privacy in the digital era by understanding the perspectives of professionals, analyzing awareness of ethical issues and compliance with privacy regulations, and identifying solutions that can overcome the ethical dilemmas that arise. This research uses a mixed approach (mixed methods) which combines qualitative and quantitative approaches. Findings from in-depth interviews show that professionals are often faced with ethical dilemmas in data management, where business interests often conflict with protecting individual privacy. Awareness of ethical issues and compliance with privacy regulations varies among organizations, with a tendency to prioritize business profits over user privacy. Massive data analysis shows that inadequate data management practices can negatively impact a company's reputation and public trust. Additionally, factors such as rapid changes in technology and regulations, trust and reputation, cooperation between the public and private sectors, and human rights also play an important role in these conflicts